Peptide profile of the sardine protein hydrolysate affects food utilization and intestinal microbiota of Nile tilapia - Ha N.* (2022)
© 2021, The Author(s), under exclusive licence to Springer Nature Switzerland AG.The present study evaluated effects of the degree of hydrolysis and peptide profile of sardine (Sardinella sp.) protein hydrolysates (SPH) from muscle tissue wastes on productive performance, body composition, hematological parameters, biochemical parameters of metabolism, antioxidant response, and intestinal microbiology tilapia (Oreochromis niloticus). Diets containing three SPH with different degrees of hydrolysis (low: 5.5%; intermediate: 27.9%, and high: 62.5%) were compared to a control diet with fish meal. The experimental design was completely randomized with four treatments and five repetitions. One hundred eighty tilapia juveniles (6.16 ± 2.0 g) were distributed in 20 polyethylene tanks of 70 l of useful volume and were evaluated during 56 days. No direct relationship was observed between the degree of hydrolysis of SPH and fish productive performance. Feed consumption was reduced in all diets with SPH (means 53.03 g) compared to the control group (65.91 g), which impaired fish growth and metabolic reserves. Feed utilization was affected by the SPH peptide profile. SPH with a more diverse peptide profile (mean 1.40) had a feed efficiency similar to the control diet (1.22). Changes in biochemical and metabolic parameters in tissues, oxidative response, and microbial populations were observed but may be associated with the low consumption of diets containing SPH. Results suggest that it is necessary to properly characterize hydrolysates and understand their composition before applying fish feed.